PROGRAM PENGABDIAN MASYARAKAT: PELATIHAN PEMBUATAN LKPD BERBASIS GEOGEBRA CLASSROOM PADA GURU SMA KABUPATEN MENTAWAI UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) SISWA - Suerman . (Jurnal Edukasi dan Penelitian Matematika, 2021)
Based on preliminary studies, the teachers of Senior High School in Mentawai district are not familiar with media and digital learning resources based on Higher Order Thinking Skills (HOTS) which are ideally used in the 4.0 revolution era. This is because the location is in the islands, far from the capital city of the Sumatera Barat Province,  and the signal is often unstable. Therefore, it is difficult to get the latest information and to learn technology. This has an impact on the learning process that is not interesting and bother the achievement of learning objectives. One of the efforts that can be done is to provide training to teachers through the Tri Dharma college activities, namely community service. The topic in this training is the Making of Digital Student Worksheet (LKPD) in the Revolution Era 4.0 and the New Normal Era Based on the Geogebra Classroom Application. Geogebra Classroom application is very suitable for making LKPD learning mathematics. The Digital LKPD should also be equipped with materials and questions that are expected to be able to increase students' HOTS. In this activity, training participants will receive material about Geogebra, and will create LKPD based on Geogebra. This Digital LKPD is useful for learning during the Covid-19 period because it avoids a lot of people's touch.Keywords-HOTS, Pengabdian Masyarakat, GeoGebra, Student Worksheet